2013
DOI: 10.1016/j.rinphs.2013.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Capsule shell material impacts the in vitro disintegration and dissolution behaviour of a green tea extract

Abstract: PurposeIn vitro disintegration and dissolution are routine methods used to assess the performance and quality of oral dosage forms. The purpose of the current work was to determine the potential for interaction between capsule shell material and a green tea extract and the impact it can have on the release.MethodsA green tea extract was formulated into simple powder-in-capsule formulations of which the capsule shell material was either of gelatin or HPMC origin. The disintegration times were determined togethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 20 publications
(23 reference statements)
1
26
0
Order By: Relevance
“…Glube et al [30] compared the dissolution rates of gelatin with HPMC capsules and found that more than 80% of the gelatin capsules dissolved in 20 min at pH 4.5, whereas less than 20% of the HPMC capsules dissolved in the same amount of time. In comparison, approximately 70% of the CRG-MD/SOR capsules dissolved in 20 min at pH 4.5, showing similar dissolution behavior to that of gelatin capsules.…”
Section: Disintegration and Dissolution Of Paracetamol Frommentioning
confidence: 99%
“…Glube et al [30] compared the dissolution rates of gelatin with HPMC capsules and found that more than 80% of the gelatin capsules dissolved in 20 min at pH 4.5, whereas less than 20% of the HPMC capsules dissolved in the same amount of time. In comparison, approximately 70% of the CRG-MD/SOR capsules dissolved in 20 min at pH 4.5, showing similar dissolution behavior to that of gelatin capsules.…”
Section: Disintegration and Dissolution Of Paracetamol Frommentioning
confidence: 99%
“…It is advisable to administer HPMC capsules on an empty stomach. Addition of digestive enzymes in the dissolution medium did not alter drug release profile for either gelatin or HPMC capsules in mixed phosphate buffer (pH 6.8), in comparison to data observed in simulated medium without enzymes [36].…”
Section: Effect Of Capsule Shell-food Interaction On Release Profilementioning
confidence: 62%
“…Cations in acetate buffer did not have any negative impact on HPMC shell material. However, gelatin capsules disintegrated comparatively faster [36]. Disintegration time of spiranomycin loaded HPMC capsules in acidic medium (pH 1.2) was not altered, even after storage at 60 °C and 75% RH for 10 d. However, disintegration time was delayed with spiranomycin encapsulated in gelatin capsules [33].…”
Section: In Vitro Disintegration Testmentioning
confidence: 99%
See 1 more Smart Citation
“…This would have created a true non-protein reference and control situation. Unfortunately, HPMC material interacts with polyphenols, limiting severely the release in simulated gastrointestinal (GI) tract condition of the HPMC capsule content [29]. This effect is absent or less pronounced in the case of gelatine capsules, which are designed to disintegrate within minutes in the GI tract.…”
Section: Discussionmentioning
confidence: 99%